2022
DOI: 10.1002/jcsm.12914
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of dystrophin isoform deficiency in motor function in Duchenne muscular dystrophy

Abstract: Background Duchenne muscular dystrophy (DMD) is caused by DMD mutations leading to dystrophin loss. Full‐length Dp427 is the primary dystrophin isoform expressed in muscle and is also expressed in the central nervous system (CNS). Two shorter isoforms, Dp140 and Dp71, are highly expressed in the CNS. While a role for Dp140 and Dp71 on DMD CNS comorbidities is well known, relationships between mutations expected to disrupt Dp140 and Dp71 and motor outcomes are not. Methods Functional outcome data from 387 DMD b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
2
18
1
Order By: Relevance
“…The aim of this study was to use a systematic approach to establish the possible effect of these variables on the NSAA scores by subdividing the cohort according to age, site of mutation and CS treatment. In agreement with recent findings [8], we also found that patients with mutations affecting more dystrophin isoforms (Dp427, Dp140 and Dp71) achieved lower maximum scores compared to those with mutations in the first part of the gene in whom only Dp427 was involved (21.6 vs 27.0). Patients with mutations affecting Dp427 and Dp140 but not Dp71 had intermediate scores.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…The aim of this study was to use a systematic approach to establish the possible effect of these variables on the NSAA scores by subdividing the cohort according to age, site of mutation and CS treatment. In agreement with recent findings [8], we also found that patients with mutations affecting more dystrophin isoforms (Dp427, Dp140 and Dp71) achieved lower maximum scores compared to those with mutations in the first part of the gene in whom only Dp427 was involved (21.6 vs 27.0). Patients with mutations affecting Dp427 and Dp140 but not Dp71 had intermediate scores.…”
Section: Plos Onesupporting
confidence: 93%
“…The variability has been reported as possibly due to a number of variables [8]. Most DMD patients start corticosteroid treatment (CS) between the age of 4 and 6 years and this may boost the possibility of an improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest a potential relationship between DMD mutations predicted to have a differential impact on dystrophin isoform production and different patterns of motor function and age at presentation in boys with DMD, 44 and this could also play a role in genotype effects that arise during clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other DMD genotype classes, and genetic modifiers at other loci 42,43 have been shown to impact functional outcomes and might also be important as prognostic factors in a clinical trial setting. Recent data suggest a potential relationship between DMD mutations predicted to have a differential impact on dystrophin isoform production and different patterns of motor function and age at presentation in boys with DMD, 44 and this could also play a role in genotype effects that arise during clinical trials.…”
Section: Limitationsmentioning
confidence: 99%